Android-Based E-Booklet Development: To Improve Learning Outcomes in Geography Subjects - Saruksuk, Torang; Tambunan, Hamonangan; Sugiharto (LPPM STKIP Kusuma Negara, 2024)
This research aims to determine (1) the feasibility of e-booklets and (2) their effectiveness. Types of R&D research include the include the Borg and Gall development models. The research subjects were material experts, media experts, learning design experts, and two class X students of SMA Negeri 1 Silimakuta. The research object is an Android-based e-booklet. The research results show: (1) learning material expert test in very good classification (87.85%), (2) learning media expert test in good classification (81.67%), and (3) learning design expert test in very good classification (86.11%). The results of proposing a hypothesis prove that: (1) Android-based e-booklets are suitable for use; (2) there is a significant difference between the learning outcomes of students who use e-booklets and conventional methods. The posttest results obtained tcount = 2.214 at a significant level (alpha = 0.05) with ttable = 1.99, so tcount > ttable. The average effectiveness of learning outcomes when using Android-based e-booklets is 80.28%. Meanwhile, the group of students who used conventional methods was 74.91%. Using an Android-based e-booklet is more effective in increasing student competency in remote sensing material than without using an Android-based e-booklet.